The moderating effects of internal and perceived external sanction threats on the relationship between deviant peer associations and criminal offending - Liu, Ruth Xiaoru (Western criminology review, 2003)
Integrating social learning and deterrence literatures, the present study hypothesizes a circumstance in which aspects of sanction threats mitigate the influence of deviant peers on criminal offending. Multiple regression analyses of the National Youth Survey (Wave VI, 1984) yielded results generally consistent with the hypothesized relationships: 1) Deviant peers predict self-offending after controlling for previous offending and other common antecedent variables. 2) Individuals who perceive higher internal sanction threat and who anticipate greater disapproval of parents and coworkers are less vulnerable to deviant peer influence. 3) While internal sanction threat and perceived disapproval of parents and coworkers simultaneously reduce deviant peer influence on selfoffending, the strongest reduction effect is observed for internal sanction threat, followed by perceived disapproval of parents and coworkers respectively. 4) Perceived threat of formal arrest reduces peer effect on criminal offending only when internal sanction threat is weak. These findings are discussed in light of theoretical contributions and policy implications.